2023
DOI: 10.3389/fphys.2023.1109587
|View full text |Cite
|
Sign up to set email alerts
|

Six weeks of N-acetylcysteine antioxidant in drinking water decreases pathological fiber branching in MDX mouse dystrophic fast-twitch skeletal muscle

Abstract: Introduction: It has been proposed that an increased susceptivity to oxidative stress caused by the absence of the protein dystrophin from the inner surface of the sarcolemma is a trigger of skeletal muscle necrosis in the destructive dystrophin deficient muscular dystrophies. Here we use the mdx mouse model of human Duchenne Muscular Dystrophy to test the hypothesis that adding the antioxidant NAC at 2% to drinking water for six weeks will treat the inflammatory phase of the dystrophic process and reduce path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…N- acetylcysteine (NAC), an intracellular antioxidant, scavenges ROS, protecting against oxidative damage. Studies have shown that NAC can alleviate skeletal muscle inflammation and improve muscle mass in patients with Duchenne muscular dystrophy [ 38 ]. In this study, NAC successfully restored motility and muscle fiber organization in SPL-deficient worms but did not improve mitochondrial morphology or the imbalance of mitochondrial dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…N- acetylcysteine (NAC), an intracellular antioxidant, scavenges ROS, protecting against oxidative damage. Studies have shown that NAC can alleviate skeletal muscle inflammation and improve muscle mass in patients with Duchenne muscular dystrophy [ 38 ]. In this study, NAC successfully restored motility and muscle fiber organization in SPL-deficient worms but did not improve mitochondrial morphology or the imbalance of mitochondrial dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…However, NAC administration was accompanied by a significant reduction in body and muscle weight in mdx mice [115], generating concerns regarding its use in patients. The question is debated since it has been recently demonstrated that NAC decreases the abnormal fiber branching responsible for mdx fiber hypertrophy, thus preventing the increase in muscle mass characteristic of the dystrophinopathies [116].…”
Section: The Key Role Of the Antioxidant Defense System In Dystrophic...mentioning
confidence: 99%
“…In addition, attenuated myocardial inflammation and fibrosis and improved cardiomyocyte calcium handling have been described after NAC treatment [58]. NAC has also been observed to improve lung function in mdx [51]. However, in addition to individual effects, combinations of amino acids may have added value as a therapeutic strategy.…”
Section: Pre-clinical Studies Evaluating Amino Acids and Derivatives ...mentioning
confidence: 99%